Ne bis in idem versus independence between instances: real or putative conflict? - Silveira de Medeiros, Alice (Universidad Nacional del Litoral, 2021)
At the center of the discussion about the viability – or not – of the accumulation of punishments and sanctions by the same facts is found the called principle of independence between the instances. One analyses some of the events that are related to the consecration of such principle; and, because of the content and of the implications of what has been agreed to be called ne bis in idem, it is verified that there is an incompatibility between these two institutes so, therefore, it is proposed that there should be a possible interpretation beginning from the collision law proposed by Robert Alexy.